2017
DOI: 10.3389/fncel.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Cognitive Impairments after Early-Life Stress Are Shaped by Inherited Differences in Stress Reactivity

Abstract: Early-life stress (ELS) has been associated with lasting cognitive impairments and with an increased risk for affective disorders. A dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis, the body’s main stress response system, is critically involved in mediating these long-term consequences of adverse early-life experience. It remains unclear to what extent an inherited predisposition for HPA axis sensitivity or resilience influences the relationship between ELS and cognitive impairments, and which n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 120 publications
1
5
0
Order By: Relevance
“…Yet, we cannot exclude changes in HPA axis activity early in life as we did not assess corticosterone levels shortly after the stress paradigm. Evidence from other studies, in fact, point to an early onset of HPA axis dysregulation originating during the stress hyporesponsive period (SHRP; P2–12) with lasting consequences of neuroendocrine programming into adulthood, similar to our study (Sapolsky and Meaney, 1986; McIlwrick et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Yet, we cannot exclude changes in HPA axis activity early in life as we did not assess corticosterone levels shortly after the stress paradigm. Evidence from other studies, in fact, point to an early onset of HPA axis dysregulation originating during the stress hyporesponsive period (SHRP; P2–12) with lasting consequences of neuroendocrine programming into adulthood, similar to our study (Sapolsky and Meaney, 1986; McIlwrick et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…One hour later, mice were exposed to testing trial in which they were allowed to explore one familiar object and one new novel object for 10 min. Mice with total exploratory times (TETs) of <5 s per object [29], or showing more than a 30% difference between two objects within 10 min during training trials, were excluded. The recognition index (RI) was the time that animals spent with the novel object (TN) divided by the total time spent exploring the familiar objects (TF) and TN in the testing trial (i.e., RI = TN/(TN + TF)).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to early-life stress (ELS) has long-lasting effects on brain structure and function and increases the risk for psychiatric illness later in life [1][2][3]. Human and rodent studies have demonstrated that stress during sensitive developmental periods impacts mood [2][3][4][5], cognition [6][7][8][9][10], and the neuroimmune system [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%